Effects of resisted vs. conventional sprint training on physical fitness in young elite tennis players - Moya-Ramon, M.; Nakamura, F. Y.; Teixeira, A. S.; Granacher, U.; Santos-Rosa, F. J.; Sanz-Rivas, D.; Fernandez-Fernandez, J. (Journal of Human Kinetics, 2020)
This study aimed to compare the effects of 6-week resisted sprint (RST) versus conventional (unresisted) sprint training (CG) on sprint time, change of direction (COD) speed, repeated sprint ability (RSA) and jump performance (countermovement jump (CMJ) and standing long jump (SLJ)) in male young tennis players. Twenty players (age: 16.5 ± 0.3 years; body mass: 72.2 ± 5.5 kg; body height: 180.6 ± 4.6 cm) were randomly assigned to one of the two groups: RST (n = 10) and CG (n = 10). The training program was similar for both groups consisting of acceleration and deceleration exercises at short distances (3-4 m), and speed and agility drills. The RST group used weighted vests or elastic cords during the exercises. After 6 weeks of intervention, both training regimes resulted in small-to-moderate improvements in acceleration and sprint ability (5, 10, 20 m), SLJ and CMJ performances, COD pivoting on both, the non-dominant (moderate effect) and the dominant (small effect) foot, and the percentage of decrement (small effects) during a RSA test. Between-group comparisons showed that the SLJ (Delta = 2.0%) and 5 m sprint time (Delta = 1.1%) improved more in the RST group compared with the CG group. This study showed that 6 weeks of RST or unresisted training are time-efficient training regimes for physical improvements in young male tennis players.